Frailty, malnutrition, and the endocrine system impact outcome in patients undergoing aortic valve replacement. Issue 1 (18th June 2021) - Al‐Kassou, Baravan; Shamekhi, Jasmin; Weber, Marcel; Germeroth, Jana; Gillrath, Jana; Feldmann, Katharina; Sedaghat, Alexander; Werner, Nikos; Treede, Hendrik; Becher, Marc Ulrich; Tiyerili, Vedat; Grube, Eberhard; et al.
Abstract: Background: Frailty is a multidimensional syndrome that affects mortality after aortic valve replacement (AVR). Malnutrition is often associated with the development of frailty. However, data regarding the association of frailty with nutritional status and underlying endocrinological dysregulation in patients with severe aortic valve stenosis are limited. Objectives: We aimed to systematically screen for frailty and malnutrition, to evaluate for underlying endocrinological disorders and inflammation, and to assess the ability of these parameters to predict outcomes after AVR. Methods: Our study included 373 patients undergoing transcatheter and surgical AVR. Frailty was assessed using the Fried Frailty Phenotype (FFP), Essential Frailty Toolset, Lawton‐Brody, and Katz Index. Malnutrition was measured using the Mini Nutritional Assessment (MNA‐LF) and Controlling Nutritional Status. Outcomes of interest were 30‐day and one‐year mortality. Results: The prevalence of frailty ranged from 6.4% to 65.7% and malnutrition from 5.9% to 10.5%, depending on the evaluation tool. Both parameters were associated with higher levels of cortisol and parathormone as well as lower levels of IGF‐1, testosterone, DHEAS, and c‐reactive protein. Malnutrition was associated with increased 30‐day mortality, and both frailty and malnutrition with increased one‐year mortality. In a multivariate analysis, malnutrition measured by the MNA‐LF (OR: 2.32 [95%CI: 1.19–4.53], p  = 0.01) and frailty as assessed by the FFP (OR: 1.42 [95%CI: 1.02–1.96], p  = 0.03) were independent predictors of one‐year mortality. Conclusion: The prevalence of frailty and malnutrition varies significantly depending on the assessment tool. Both syndromes share common endocrinological alterations. Frailty and malnutrition are independent risk factors for mortality after AVR.